2015
DOI: 10.1139/cjfr-2014-0388
|View full text |Cite
|
Sign up to set email alerts
|

Hard pine stem rusts on lodgepole pine at a site-preparation study in sub-boreal British Columbia: effects over 24 years

Abstract: Site preparation can improve lodgepole pine (Pinus contorta var. latifolia Engelm. ex S. Watson) survival and growth; however, we lack information regarding possible interactions between treatment effects and the impacts of western gall rust (Endocronartium harknessii (J.P. Moore) Y. Hirats.) and comandra blister rust (Cronartium comandrae Peck). Mechanical and burning techniques examined over 24 years at a sub-boreal British Columbia site did not significantly increase rust infection rates or characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
1
5
1
Order By: Relevance
“…At Bednesti, false toadflax was found only in older, less-disturbed pine stands, providing tentative support for the view that soil disturbance could reduce this host in the early years when pines are most liable to infection. Contrary to these findings and an earlier analysis by Reich et al (2015),…”
Section: Management Indicator Speciescontrasting
confidence: 99%
“…At Bednesti, false toadflax was found only in older, less-disturbed pine stands, providing tentative support for the view that soil disturbance could reduce this host in the early years when pines are most liable to infection. Contrary to these findings and an earlier analysis by Reich et al (2015),…”
Section: Management Indicator Speciescontrasting
confidence: 99%
“…Extensive damage to individual pine trees in older operational plantations or in replicated experiments has also been observed in other BC studies [14,19,40,46] and has been forecast to intensify under climate change [17]. We found that rates of loss for pine due to killing agents alone either matched the expected rate of loss (TIPSY projections [34]), or were as much as twice as high as expected in the largest diameter trees.…”
Section: Discussionsupporting
confidence: 78%
“…Warmer and wetter conditions in spring and summer months favor hard pine rusts [38][39][40], the dominant forest pathogens we observed, which combined affected 15% of all lodgepole pine trees. In the only prior extensive survey of forest disturbances in managed stands in BC, a study conducted in the early 1990s, 6% of pine trees were found to be affected by hard pine rusts across the SBS zone [41].…”
Section: Discussionmentioning
confidence: 99%
“…Summary : A trend towards a greater frequency of years with more spring and summer precipitation and higher overnight minimum temperatures in late summer throughout interior BC has reduced the period between rust wave years (Woods, 2011) to as little as three years on some sites (Reich et al, 2015). This represents an apparent change in disease behaviour from that observed earlier in BC and farther south in the Rocky Mountain states where outbreaks of comandra blister rust had been considered rare (Krebill, 1968).…”
Section: Applying the Conceptual Framework Of Climate Involvement To ...mentioning
confidence: 99%
“…Wave years for other stem rusts, including white pine blister rust ( Cronartium ribicola ), comandra and stalactiform blister rust, require moderate temperatures and moist conditions in mid‐ to late summer (Hunt, 2004; Krebill, 1968; Van Arsdel et al, 1956) during the vulnerable basidiospore stage of the rust life cycle (Peterson, 1971). Optimum overnight minimum temperatures are also critical for wave year events (Reich et al, 2015). Long‐term climatic trends at Fort St. James, BC, a weather station located near the centre of the latitudinal range of lodgepole pine in western North America (Wheeler & Critchfield, 1985), indicate a 7℃ increase in summer overnight minimum temperatures over the period of 1895–2019 (V. Foord, pers comm., June 2, 2020).…”
Section: Applying the Conceptual Framework Of Climate Involvement To ...mentioning
confidence: 99%